2. Tożsamość państwowa czy komunikacja międzykulturowa? Problemy językowe we współczesnym Kirgistanie .......... 185 - Żak, Elżbieta (Kirgistan – oblicza transformacji, 2020)
National Identity or Intercultural Communication? Language ISSUES IN CONTEMPORARY KYRGYZSTAN In the present paper the position of the Russian language in the Republic of Kyrgystan is considered, based on the heritage of the former Soviet Union and in the new political and social contexts in this country. The collapse of the Soviet Union has caused transformations in all fields, and it has also brought about language problems in Central Asian Republics. In the Soviet past, the Russian language had even been an important element of the campaign of cultural russification, but in Kyrgystan it also became the language of progressive culture, language of education, technological development, and business relations. The Russian language has maintained its official status still since the year 1989, but because of the need to force and create an independent national identity, the government has been obliged to implement a lot of reforms in order to develop the Kyrgyz language. That is why we can observe significant political processes, which had determined the government’s work focused on development of Kyrgyz language with a big challenge of creating its systematic structure and the proper administrative, legal, and technological terminology in this national language. What is focused on are educational problems, including the Russian speaking government clerks and officials, and also the low level of contemporary school education in Kyrgyzstan and social and economic perspectives without the knowledge of Russian.